Evaluation of the implementation of a relationship and sexuality education project in Western Australian schools: protocol of a multiple, embedded case study - Burns, Sharyn K.; Hendriks, Jacqueline; Mayberry, Lorel; Duncan, Scarlett; Lobo, Roanna; Pelliccione, Lina (BMJ Open, 2019)
Introduction There is recognition of the importance of comprehensive relationships and sexuality education (RSE) throughout the school years worldwide. Interventions have found some positive outcomes; however, the need for a greater focus on positive sexuality and relevant contemporary issues has been identified by teachers and students. The Curtin RSE Project provides training for teachers and preservice teachers and supports schools through training and advice to implement comprehensive school health promotion (CSHP) focusing on RSE allowing schools to develop programmes relevant to their school community. To examine contemporary phenomenon within a real word context, a case study design will be used to measure implementation. This paper will describe the protocol for a multiple, embedded case study to measure the implementation of CSHP focusing on RSE in a purposive sample of Western Australian schools. Methods and analysis This mixed methods study will include a multiple, embedded case study. Schools (n=3–4) will be purposively selected from within Western Australia based on their capacity to commit to implementing RSE as a case study school. Data will be collected from students (Grade 6 for primary school; Grades 7–12 for secondary school); teachers and other key staff and parents. Methods include school climate and school curriculum audits, documentation (collected with key staff at baseline and annually), interviews (parents and teachers at Year 2), focus groups (students at Year 2) and an online student survey (collected with students baseline and annually). Ethics and dissemination School principals will provide consent for school participation and staff and parents will provide individual consent. Student assent and parental consent will be obtained for student participants. Results will be disseminated through open-access reports, peer-reviewed journals and conference presentations.